Population-Based Surveillance of HIV Drug Resistance Emerging on Treatment and Associated Factors at Sentinel Antiretroviral Therapy Sites in Namibia. (1st April 2015) - Hong, Steven Y.; Jonas, Anna; DeKlerk, Michael; Shiningavamwe, Andreas; Desta, Tiruneh; Badi, Alfons; Morris, Lynn; Hunt, Gillian M.; Ledwaba, Johanna; Sheehan, Heidi B.; Lau, Kiger; Trotter, Andrew; et al.
Abstract : Objective: The World Health Organization (WHO) prospective surveys of acquired HIV drug resistance (HIVDR) evaluate HIVDR emerging after the first year of antiretroviral therapy (ART) and associated factors. Methods: Consecutive ART starters in 2009 were enrolled at 3 sentinel sites in Namibia. Genotyping was performed at start and after 12 months in patients with HIV viral load (VL) >1000 copies per mL. HIVDR outcomes were: HIVDR prevention (VL ⩽1000 copies/mL), possible HIVDR (VL >1000 copies/mL without detectable HIVDR or loss to follow-up or ART stop), and HIVDR (VL >1000 copies/mL with detectable HIVDR). Adherence was assessed using medication possession ratio (MPR). Results: Of 394 starters, at 12 months, 80% were on first-line ART, 1% died, 4% transferred out, 1% stopped ART, <1% switched to second-line, and 15% were lost to follow-up. Among patients on first-line, 77% had VL testing, and 94% achieved VL ⩽1000 copies per mL. At baseline, 7% had HIVDR. After 12 months, among patients with VL testing, 5% had HIVDR. A majority of patients failing therapy had high-level resistance to nonnucleoside reverse transcriptase inhibitors but none to protease inhibitors. All sites achieved the WHO target of ≥70% HIVDR prevention. Factors associated with not achieving HIVDR prevention were: baseline resistance to nonnucleoside reverse transcriptase inhibitors [odds ratio (OR) 3.0, P = 0.023], WHO stage 3 or 4 at baseline (OR 2.0, P = 0.012), and MPR <75% (OR 4.9, P = 0.021). Conclusions: Earlier ART initiation and removal of barriers to on-time drug pickups may help to prevent HIVDR. These data inform decisions at national and global levels on the effectiveness of first- and second-line regimens. Abstract : Supplemental Digital Content is Available in the Text.